The Personality of Antoine Augustin Cournot - Moore, Henry L. (Quarterly Journal of Economics, 1905)
Journal Article The Personality of Antoine Augustin Cournot Get access Henry L. Moore Henry L. Moore Columbia University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 19, Issue 3, May 1905, Pages 370–399, https://doi.org/10.2307/1882658 Published: 01 May 1905